Enabling people with severe mental illness to overcome barriers to access dental treatment: a qualitative study applying COM-B framework analysis. (2nd November 2022) - Brigg, Nicole; Patterson, Sue; Pradhan, Archana
Abstract: Background: The oral health of people with severe mental illness is severely compromised. Rates of premature total tooth loss and tooth decay are substantially higher than in the general population. Causation is complex, restricted access to treatment a major contributing factor. Aims: To examine factors enabling people with complex problems related to severe mental illness to attend scheduled dental appointments. Method: Qualitative semi-structured interviews were conducted with 15 service users who attended no-cost treatment at a university clinic, following oral health screening at an inner-city community mental health service. Analysis used a framework approach informed by a theoretical model of behaviour (COM-B). Results: Complex individual motivations, related variously to function, pain and/or self or social appraisal, were also influenced by expectations of treatment. Capabilities included managing "messy" life circumstances; participants overcame various psychological and physical challenges to attend treatment, enabled by opportunities of social and instrumental support. Conclusions: Genuine partnerships between agencies to provide access opportunities, in addition to individual support responsive to personal motivators and adapted to capabilities can enable access to services and improve the lives of people with severe mental illness.